The ERNCIP survey on COVID-19: Emergency & Business Continuity for fostering resilience in critical infrastructures. (July 2021) - Galbusera, Luca; Cardarilli, Monica; Giannopoulos, Georgios
Abstract: Among the many repercussions of the COVID-19 emergency to be assessed, those on critical infrastructures and the associated businesses and professions are certainly important ones. In this paper, we document the conception, implementation and outcome of a survey organized by European Commission's Joint Research Centre and entitled "COVID-19: Emergency & Business Continuity" . This was conducted in April-May 2020 with the participation of critical infrastructure experts (including professionals from the academia and research institutions, infrastructure operators and industry representatives, public authorities and members of security agencies), involved as stakeholders in the European Reference Network for Critical Infrastructure Protection (ERNCIP). Themes explored through this study include an assessment of the business continuity status and the evaluation of emergency management and disaster recovery aspects, as experienced from the perspective of different sectors, organization types and personal perceptions of the respondents.